Population genetic structure and patterns of hybridization of the rare Lupinus tidestromii and its congener L. chamissonis (Fabaceae) inform seed sourcing strategies for population augmentation and reintroduction - Aspen Workman; Eleanor A. Pardini; Lorraine S. Parsons; Stefan G. Michalski; Tiffany M. Knight; Walter Durka (Conservation Genetics, 2026)
Human activities can impact the genetic diversity of populations, making them more vulnerable to extinction. Rare species are at an increased risk of negative genetic consequences of human activities, but understanding genetic diversity in rare species requires comparison to more common congeners. Hybridization, a common phenomenon in plants, can provide genetic rescue of genetically depauperate populations or put rare species at risk of being “swamped” out of the population. Human-mediated dispersal can create novel sympatry between previously allopatric species, fostering hybridization. The endangered Tideström’s lupine ( Lupinus tidestromii Greene ), endemic to the coastal dune ecosystem of California, co-occurs and hybridizes with the more common dune bush lupine ( L. chamissonis Eschsch .). We characterized 532 individuals from sympatric and non-sympatric sites across both species’ entire geographic ranges using genotyping-by-sequencing technology to identify 1,377 single-nucleotide polymorphisms. We analyzed population structure, genetic diversity within and among populations, and hybridization between L. tidestromii and L. chamissonis . Genetic diversity was lower in L. tidestromii than in the more common L. chamissonis . Both species showed strong population structure which coincided with a deep intraspecific split between populations north and south of San Francisco. Hybridization was confirmed at all sites of co-occurrence. Evidence of hybridization at multiple non-sympatric sites indicated former co-occurrence and recent local extirpations. From these results, we make specific management recommendations for L. tidestromii . Seeds from large populations in the north can be used to augment the smaller populations in this region and to reintroduce this endangered species back to extirpated sites. Our results highlight how studies considering spatial patterns of genetic diversity, hybridization and private alleles can be used to make clear recommendations for conservation actions.

A Robust Decision-Making approach to evaluating state support for nuclear programmes under uncertainty: A UK case study - J. Mangin; M. Bluck; G. Darch; D. Roberts; S. Brown; M. Workman (Energy Policy, 2025)

Prenatal exposure to polycyclic aromatic hydrocarbons and executive functions at school age: Results from a combined cohort study - Yu Ni; Adam A. Szpiro; Christine T. Loftus; Tomomi Workman; Alexis Sullivan; Erin R. Wallace; Anne M. Riederer; Drew B. Day; Laura E. Murphy; Ruby H.N. Nguyen; Sheela Sathyanarayana; Emily S. Barrett; et al. (International Journal of Hygiene and Environmental Health, 2024)

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

Development of a tissue-engineered skin model with epidermal, dermal and hypodermal components - V. L. Workman; A-V. Giblin; N. H. Green; S. MacNeil; V. Hearnden (In vitro models, 2023)
Tissue-engineered models of skin have evolved over the past 50 years, have successfully been translated to clinical use and continue to be improved using new technologies. However, very few of these constructs incorporate a hypodermal component. The hypodermis is critical to skin homeostasis, skin function and many skin diseases, but our understanding of the hypodermis is limited in comparison to our knowledge of the epidermis and dermis, in part due to a lack of suitable in vitro models. The purpose of this study was to develop and characterise a tissue-engineered model of skin consisting of epidermal, dermal and hypodermal layers, namely a trilayer skin model. Models were produced by culturing human keratinocytes and fibroblasts on decellularised human dermis in combination with explanted human adipose tissue. Bilayer models of skin, comprising of an epidermis and dermis, had a thicker epidermal component compared to trilayer models but exhibited similar cytokeratin expression patterns (AE1/AE3 and cytokeratin 14). Addition of adipose tissue improved the appearance of the dermal-epidermal junction, increased the number of rete ridge-like features and cells maintained similar levels of proliferation (Ki-67) compared to native tissues over 28 days in culture. This technique enabled us to create a physiologically relevant model of human skin with representative morphology across the hypodermis, dermis and epidermis. This model maintained native extracellular matrix architecture, contained a heterogeneous population of cells and has the potential to be applied to a range of different applications where research questions require the inclusion of a hypodermis.

Alteration of oral microbiome composition in children living with pesticide-exposed farm workers - Ian B. Stanaway; James C. Wallace; Sungwoo Hong; Carly S. Wilder; Foad H. Green; Jesse Tsai; Misty Knight; Tomomi Workman; Eric M. Vigoren; Marissa N. Smith; William C. Griffith; Beti Thompson; et al. (International Journal of Hygiene and Environmental Health, 2023)

By the hand of the smelter: tracing the impact of decision-making in bloomery iron smelting - Ivan S. Stepanov; Lee Sauder; Jake Keen; Vanessa Workman; Adi Eliyahu-Behar (Archaeological and Anthropological Sciences, 2022)
Slag analyses from archaeological iron smelting sites are common. Rigorous analyses of iron and slag from successful experimental smelting, however, are still rare. Furthermore, thorough analyses from a series of smelts, and of the slag produced in different phases of the smelt, are exceedingly rare. The present study investigates the effect of an iron smelter’s decision-making and skills on the products of the smelting process: iron and slag. Four smelting experiments were carried out in a shaft furnace with slag tapping using iron ores from the Southern Levant. Using various analytical techniques, including portable X-ray fluorescence, optical and electron microscopy, metallography, and hardness tests enabled us to correlate the properties of the final products with adjustment of various parameters during the smelting process. The latter include airflow and charging rate, temperature, residence time in the reducing zone, ore-charcoal ratio, and control of the slag characteristics. Results obtained allowed us to empirically demonstrate the direct impact of decisions made by the smelter during the complex technological practice of bloomery smelting. Analysis also highlights the benefits of moderately reducing conditions controlled by the smelter to produce good-quality, low-carbon iron, which is particularly relevant within the geological setting of the Southern Levant.

Understanding Quality Paradigm Shifts in the Evolving Pharmaceutical Landscape: Perspectives from the USP Quality Advisory Group - Jane Weitzel; Horacio Pappa; Gregory M. Banik; Amy R. Barker; Elizabeth Bladen; Narendra Chirmule; Joseph DeFeo; Jennifer Devine; Steven Emrick; Taha Kass Hout; Michael S. Levy; Gugu N. Mahlangu; et al. (The AAPS Journal, 2021)
Recent changes in the pharmaceutical industry have led to significant paradigm shifts in the pharmaceutical quality environment. Globalization of the pharmaceutical industry, increasingly rapid development of novel therapies, and adoption of new manufacturing techniques have presented numerous challenges for the established regulatory framework and quality environment and are impacting the approaches utilized to ensure the quality of pharmaceutical products. Regulators, industry, and standards-setting organizations have begun to recognize the need to rely more on integrated risk-based approaches and to create more nimble and flexible standards to complement these efforts. They also increasingly have recognized that quality needs to be built into systems and processes throughout the lifecycle of the product. Moreover, the recent COVID-19 crisis has emphasized the need to adopt practices that better promote global supply chain resilience. In this paper, the USP Quality Advisory Group explores the various paradigm shifts currently impacting pharmaceutical quality and the approaches that are being taken to adapt to this new environment. Broad adoption of the Analytical Procedure Lifecycle approach, improved data management, and utilization of digital technologies are identified as potential solutions that can help meet the challenges of these quality paradigm shifts. Further discussion and collaboration among stakeholders are needed to pursue these and other solutions that can ensure a continued focus on quality while facilitating pharmaceutical innovation and development.

Low Static Shear Modulus Along Foliation and Its Influence on the Elastic and Strength Anisotropy of Poorman Schist Rocks, Homestake Mine, South Dakota - Katherine J. Condon; Hiroki Sone; Herbert F. Wang; J. Ajo-Franklin; T. Baumgartner; K. Beckers; D. Blankenship; A. Bonneville; L. Boyd; S. Brown; J. A. Burghardt; C. Chai; et al. (Rock Mechanics and Rock Engineering, 2020)

Erratum to: Remodelling of human atrial K+ currents but not ion channel expression by chronic β-blockade - Gillian E. Marshall; Julie A. Russell; James O. Tellez; Pardeep S. Jhund; Susan Currie; John Dempster; Mark R. Boyett; Kathleen A. Kane; Andrew C. Rankin; Antony J. Workman (Pflügers Archiv - European Journal of Physiology, 2014)

Migration characteristics of hatchery and natural-origin Oncorhynchus mykiss from the lower Mokelumne River, California - S. Casey Del Real; Michelle Workman; Joseph Merz (Environmental Biology of Fishes, 2012)

Remodelling of human atrial K+ currents but not ion channel expression by chronic β-blockade - Gillian E. Marshall; Julie A. Russell; James O. Tellez; Pardeep S. Jhund; Susan Currie; John Dempster; Mark R. Boyett; Kathleen A. Kane; Andrew C. Rankin; Antony J. Workman (Pflügers Archiv - European Journal of Physiology, 2012)

North American Agroforestry: An Integrated Science and Practice. H. E. Garrett, W. J. Rietveld and R. F. Fisher (eds.). American Society of Agronomy, Inc. Madison, WI, USA. - S. W. Workman; N. V. Thevathasan; A. M. Gordon (Agroforestry Systems, 2002)

Biphasic Material Properties of Lytic Bone Metastases - Cari M. Whyne; Serena S. Hu; Kimberly L. Workman; Jeffrey C. Lotz (Annals of Biomedical Engineering, 2000)

Inhibition of Baculoviral Disease by Plant-Mediated Peroxidase Activity and Free Radical Generation - Kelli Hoover; Kenneth T. Kishida; Louis A. DiGiorgio; Jeff Workman; Susan A. Alaniz; Bruce D. Hammock; Sean S. Duffey (Journal of Chemical Ecology, 1998)

Specificity of induced resistance in the tomato, Lycopersicon esculentum - Michael J. Stout; Kathi V. Workman; Richard M. Bostock; Sean S. Duffey (Oecologia, 1997)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)